Peran Jaksa Dalam Pelaksanaan Diversi Terhadap Pidana Anak - Simanjutak, Komis; Suriani, Suriani; Hutama Hutabarat, Dany Try; Alpadira, Rinda (Magister Hukum Universitas Semarang, 2022)
The examine target to decide the role of the prosecutor in the implementation of diversion so that you can encourage the realization of a diversion settlement a good way to decrease the negative effect on youngsters if the case is going to court. The public prosecutor is obligated to make diversion efforts with the aid of summuning and/or supplying case resolution thru diversion to the kid and/or discern/father or morher as well as the sufferer or baby of the victim and/or parent/father or mother. Because of this, the role of the public prosecutor in sporting out diversion is not best limited to releasing responsibilities, but should be greater active to inpire the conclusion of a diversion agreement. This research is essential so that the implementation of diversion is prioritized within the settlement of kids instances by way of the general public prosecutor. This take a look at uses emperical juridical research strategies. This research has novel fee because it discusses in particular about the role of prosecutors in imposing diversion within the area. Based at the effects of the observe, it could be seen that the position of the prosecutor in the implementation of diversion is as a facilitator by way of seeking to reconcile the victim, in addition to the victims circle of relatives, in opposition to crook acts committed with the aid of youngsters. Penelitian ini bertujuan untuk mengetahui peran jaksa dalam pelaksanaan diversi guna upaya mendorong terwujudnya kesepakatan diversi sehingga bisa meminimalisir akibat kurang baik pada anak apabila perkaranya hingga ke pengadilan. Penuntut umum harus melaksanakan upaya diversi dengan memanggil dan/ ataupun menawarkan penyelesaian kasus lewat diversi kepada anak dan/ ataupun orang tua/ wali dan korban ataupun anak korban dan/ ataupun orang tua/ wali. Jaksa Penuntut umum dalam melakukan diversi tidak cuma sebatas membebaskan kewajiban saja, tetapi wajib lebih aktif dalam mendorong terwujudnya kesepakatan diversi. Penelitian ini penting dilakukan supaya pelaksanaan diversi diutamakan pada penyelesaian permasalahan anak oleh jaksa penuntut umum. Penelitian ini menggunakan tata cara penelitian yuridis empiris. Penelitian ini mempunyai nilai kebaharuan sebab mangulas secara khusus mengenai peran jaksa dalam penerapan diversi. Berdasarkan pada penelitian yang dilakukan hingga dapat diketahui bahwa peran jaksa dalam penerapan diversi menjadi fasilitator dengan berupaya mendamaikan anak/ orangtua/ wali dengan korban/ orangtua/ wali atas perbuatan pidana yang dilakukan oleh anak.